2016
DOI: 10.3109/02770903.2016.1155217
|View full text |Cite
|
Sign up to set email alerts
|

Enabling and hindering factors influencing adherence to asthma treatment among adolescents: A systematic literature review

Abstract: Objectives: The aim of this systematic literature review is to study the enabling and hindering factors influencing adherence to asthma treatment among adolescents. Furthermore, it explores the role of caregivers and the healthcare provider in terms of supporting adolescents to manage and live with asthma. Data sources: The literature review was conducted using the MeSH terms asthma, adherence, health literacy, behavior, adolescents, tools, healthcare provider, caregiver, peer influence, self-management, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 49 publications
3
48
0
1
Order By: Relevance
“…These concerns also seem particularly relevant for young patients with asthma. Consistent with the systematic review by Ahmad et al [80] on adherence to asthma treatment among adolescents, our findings suggest that adolescents may have additional barriers to adherence and engagement, such as feeling embarrassed about their asthma, social stigma and dependence on their peer group; and addressing these barriers can be highly complex as these may be influenced by psychosocial factors [81]. These findings also suggest that treatment beliefs and concerns can differ with age.…”
Section: Discussionsupporting
confidence: 88%
“…These concerns also seem particularly relevant for young patients with asthma. Consistent with the systematic review by Ahmad et al [80] on adherence to asthma treatment among adolescents, our findings suggest that adolescents may have additional barriers to adherence and engagement, such as feeling embarrassed about their asthma, social stigma and dependence on their peer group; and addressing these barriers can be highly complex as these may be influenced by psychosocial factors [81]. These findings also suggest that treatment beliefs and concerns can differ with age.…”
Section: Discussionsupporting
confidence: 88%
“…Medication adherence behavior falls into intentional (no perceived need, concerns about side effects) and unintentional nonadherence (forgetting or poor inhaler technique), 41 and both types of nonadherence affect children and adolescents with asthma. Positive family functioning, routines and communication skills, and positive parental medication efficacy beliefs have all been associated with improved medication adherence, 42 whereas high perceived burden of treatment or negative health beliefs including anxiety or concerns about medication use, 43,44 higher levels of psychological distress or depressive symptoms in caregivers has been associated with poorer adherence outcomes 35,45 .…”
Section: Patient and Family Level Factorsmentioning
confidence: 99%
“…In addition, children and adolescents with asthma present unique challenges to medication adherence. Adolescents may report erroneous medication beliefs (eg, medications are for when one is sick, “growing out of asthma,”) , poor knowledge, forgetting, lack of routines, hurrying, competing social priorities, difficulties communicating with healthcare providers, poor health literacy, concerns for side effects and social stigma associated with having asthma and using inhalers 41,47–50 . In addition, adolescents may feel that using controller medication may create a dependence 51 .…”
Section: Patient and Family Level Factorsmentioning
confidence: 99%
“…The importance of quantity and frequency of the dosages should also be kept in mind in order to assure adherence. In asthma, one review reported that increasing number of medications was associated with lower adherence (Ahmad & Sorensen, 2016). In children with ADHD, increased dose frequency of ADHD medication had a negative effect on adherence (Gau et al, 2008).…”
Section: Factors With Possible Influence On Adherence Behaviour In Asmentioning
confidence: 99%